Case study: company analysis Wakaka Cafe Sdn Bhd / Farrah Adilla Hanum Zulkapli … et al.] - Zulkapli, Farrah Adilla Hanum; Saiful Bahri, Balqis; Jamal, Nurulhuda (2023)
After the spread of the COVID-19 pandemic, now entrepreneurs and small traders are trying to rebuild their finances despite the numerous challenges and risks that they had to face before. This case study is being conducted to see how the Business Model Canvas (BMC) may be used to put the concepts gained in this course into practise. For this case study, we chose to study about Wakaka F&B business which was established since 2017. Wakaka F&B is a business which sells beverages and waffles. Wakaka has branches almost in every state in Malaysia including Malacca, Johor, Selangor, Perlis, Kedah, Penang, Langkawi, Perak, Kelantan, and Pahang. However, even though it has many branches, Wakaka F&B still can't get a lively reception like other local F&B businesses such as Tealive, and Chatime. Other than because of the lockdown, Wakaka also face other major problems which is problems in workers, competitor, lack of promotion, beverages are too sweet, and bad customer service. In order to overcome this situation, we suggest some solutions including hiring employees who fit in at your company, adding new products, leveraging social media, adding sugar-level options, and improving customer service.